Usuários em cena: um estudo psicossocial a respeito da participação dos conselheiros representantes dos usuários no Conselho Municipal de Saúde, de Belo Horizonte - Fabiana Lucia Campos Baptista (2006)
This work introduces the result of a research on the participation of representative advisers of users in the Municipal Health Council of Belo Horizonte. It has particularly, attempted, to identify the meaning attributed by the user council concerning his/her participation inside CMS-Belo Horizonte. Semi-structured interviews with advisers, minute analysis of extraordinary and ordinary meetings, and observation of meetings and Technical Chambers were used as research tools. Data were analyzed based on a model of political awareness developed by Sandoval (2001), increased of the Pizzorno (1975) contribution. After these analysis, it was concluded that the act of participating for the user adviser implies being familiar with health politics, demanding their effective accomplishment, discussing, them in, meetings as well as suggesting methods that could actually be implemented in community. The construction of these meanings lies upon a prior political background, in local and district commissions, reciprocal relationships established with community, adviser interaction with other segments, their understanding of their adviser roles, and identification with health problems, faced by the community. All these issues contributed to form the idea of participation developed by the user adviser and have been assisting in a way that he/she establishes a participative political awareness.